2020
DOI: 10.1016/j.nano.2020.102235
|View full text |Cite
|
Sign up to set email alerts
|

Ion channel formation by N-terminally truncated Aβ (4–42): relevance for the pathogenesis of Alzheimer's disease

Abstract: Aβ deposition is a pathological hallmark of Alzheimer's disease (AD). Besides the full-length amyloid forming peptides (Aβ 1-40 and Aβ 1-42 ), biochemical analyses of brain deposits have identified a variety of N-and C-terminally truncated Aβ variants in sporadic and familial AD patients. However, their relevance for AD pathogenesis remains largely understudied. We demonstrate that Aβ 4-42 exhibits a high tendency to form β-sheet structures leading to fast selfaggregation and formation of oligomeric assemblies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…These channels are non-selective and can be extremely large [3, 4, 20, 24, 34]. Channel formation is frequently cited as a molecular mechanism underlying AD [2, 6, 14, 15, 18, 19], but it is usually implied that the channels are formed in the plasma membrane, which does not explain many phenomena associated with the disease [45]. Our hypothesis suggests that amyloid membrane channels are formed in lysosomal membranes rather than in plasma membranes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These channels are non-selective and can be extremely large [3, 4, 20, 24, 34]. Channel formation is frequently cited as a molecular mechanism underlying AD [2, 6, 14, 15, 18, 19], but it is usually implied that the channels are formed in the plasma membrane, which does not explain many phenomena associated with the disease [45]. Our hypothesis suggests that amyloid membrane channels are formed in lysosomal membranes rather than in plasma membranes.…”
Section: Discussionmentioning
confidence: 99%
“…6). Some beta-amyloid fragments are able to form membrane channels, and some are not [18, 24, 41, 42], so endocytosed beta-amyloid can be degraded by lysosomal proteases into both channel-forming and non-channel-forming fragments (Fig. 6, dichotomy 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, miR-485-5p overexpression induced the decrease in Aβ42 and Aβ40 concentration and the increase in the number of pericytes. It is known that Aβ deposition is a typical feature of AD pathology [ 37 ]. Thus, we concluded that miR-485-5p alleviates the progression of AD in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Peptide oligomerization was also monitored by electron microscopy, as previously described [ 38 , 66 , 71 ]. Five microliters of either monomeric or oligomeric preparations of the different Aβ peptides were placed onto carbon-coated 400 mesh Cu/Rh grids (Ted Pella, Inc., Redding, CA) and stained with 1% uranyl acetate in distilled water (Polysciences, Inc., Warrington, PA).…”
Section: Methodsmentioning
confidence: 99%